Large-panel buildings after years of exploitation. Selected problems of repairs - Ligęza, Wiesław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
In the paper there are presented problems of repairs for existing large-panel buildings within the light of: damage of joints between load-bearing and façade walls, structural requirements for functional modernization, damage of layer joints in load-bearing and façade three-layer walls, new repair questions within the aspect of executed buildings’ thermal modernization.